2011
DOI: 10.1080/00222933.2011.590946
|View full text |Cite
|
Sign up to set email alerts
|

Development rates, larval survivorship and wing length ofCulex pipiens(Diptera: Culicidae) at constant temperatures

Abstract: In this study, the effects of rearing temperature on survival and development rate of pre-imaginal stages and on wing length of adult Culex pipiens (Diptera: Culicidae) were evaluated. Larvae I were reared until adult emergence at seven constant temperatures between 7 and 33 • C. The highest survival was found at 25 • C. The development rate of the immature stages decreased with increasing temperature until 30 • C. The threshold temperature and thermal constant were, respectively, 5.2 • C and 186.5 degree-days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 32 publications
6
65
0
Order By: Relevance
“…By using two mosquito population models to replicate the current observation data and applying GCM data, our results indicated that under future climate conditions, active mosquito populations will decrease and that the active season will be shortened. This is because of an increase in the number of days exceeding the suitable temperature for growing, as suggested by experimental data [ Oda et al ., ; Loetti et al ., ], and is consistent with the findings of Marini et al . [], who suggested a decrease in active C. pipiens populations under an average temperature increase of 2.0°C.…”
Section: Discussionsupporting
confidence: 93%
“…By using two mosquito population models to replicate the current observation data and applying GCM data, our results indicated that under future climate conditions, active mosquito populations will decrease and that the active season will be shortened. This is because of an increase in the number of days exceeding the suitable temperature for growing, as suggested by experimental data [ Oda et al ., ; Loetti et al ., ], and is consistent with the findings of Marini et al . [], who suggested a decrease in active C. pipiens populations under an average temperature increase of 2.0°C.…”
Section: Discussionsupporting
confidence: 93%
“…Among the other variables, rainfall and mean air temperature did not show any significant effect on CS. This was expected since wing size seems to be more affected by the aquatic microclimate of the immature stage (Loetti et al, 2011; Stephens and Juliano, 2012; Sutcliffe and Benedict, 2012). …”
Section: Discussionmentioning
confidence: 91%
“…This is likely to result from the acceleration of mosquito development rates driven by higher temperatures [20]. Higher temperatures during the late period (encompassing the main period of mosquito host seeking activity) are similarly associated with increased season length, but also with a decrease in total abundance.…”
Section: Discussionmentioning
confidence: 99%